Compostos voláteis emitidos pelo alho são retidos em água e controlam Meloidogyne incognita - Maciel, Wendel Oliveira (2016)
Volatiles are importants on the relationship between microorganisms, among plants and microorganisms and are toxic to plant pathogenic organisms, especially plant parasitic nematodes. The nematode Meloidogyne incognita,whichcauses losses to several crops woldwide, including Brazil, showed high immobility and mortality of second stage juveniles (J2) when mixed to aquaeous íons macerates of several garlic concentrations, in pure solution of alcohol 40% exposed to one to forty-eight hours. When volatile emmittions from the diverse concentrations of garlic macerates beside alcohol 40% in mitures with the substract, were storaged at the mixture surface, the volatiles either from garlic or to alcohol 40%, caused J2 immobility above 95% and J2 mortality 73% to 99%. The J2 exposed to those volatiles and inoculated on tomatoes showed significat reduction of egg numbers from trataments of 10% garlic concentration to 40% (macerated) in water, beside 5 g of macerated garlic in alcohol 40% and plain solution of alchol 40% in water compared to control. The J2 infectivity obstainned with the same treatments, except 10% of garlic, was singnificatly reduced also to control. Water which was exposed to those volatiles and mixed with J2 suspension of M. incognita, caused immobility from 95% to 100% and mortality from 74% to 99% in all treatments. Chromatographic analysis an CGMS of diluted volatiles in exposed water to garlic emmittions as well as in vapor phase and in aqueous maceraet garlic, revealled the presence of 32 molecules mainlly distributed to classes of alcohol, aldehide and sulfurates. The mostly intensive compoudes were is dissulfit of methyl allyl, dissulfite diallyl, 3-vinyl -1-2- dithiacyclohex - 5 - ene, trissulfite of diallyl, dissulfite of di (1 propenil) (trans), 2 – propen -1-tiol or alithiol, sufite of methyl allyl, 2 ethyl -1- hexanal and one unidenfied compound. The sulfur class of molecules was the greatest emittion source. In the water exposed to garlic volatile emittions were found eleven compounds and the most intense were dissulfite of dialila and 2-ethyl-1-hexanol. This is the first characterization of volatile molecules diluted in water by simple exposure and toxic to plant parasitic nematode.